Shades of the Assessment of Slavic Loanwords in Southern Aukštaitian Subdialects - Ragaišienė, Vilija (Slavistica Vilnensis, 2023)
The article discusses the connotation, context of usage and tendencies of loanwords (nouns and adjectives) from Slavic languages used in the subdialects of the Southern Aukštaitians. The research conducted revealed that the constant connotation is usually characteristic of loanwords that name persons and other living beings by their character traits, habits and inclinations, less often by their physical characteristics. Loanwords acquire a contextual connotation in contexts (combinations of words and sentences) in which the physical characteristics and appearance of the object under discussion (a person or other living being) are assessed from a certain aspect. The positive or negative shade of the assessment of loanwords with constant connotation can be used not only in a word taken separately but also in a wider context of usage. Loanwords of Southern Aukštaitian subdialects usually have a negative connotation. The spectrum of the assessment of the object in question is quite wide: from teasing to ridicule or even bullyin. Loanwords in certain contexts are used as having a greater emotional expression than Standard language words.
Keywords: loanword; Slavism; connotation; subdialect; Southern Aukštaitians